2021
DOI: 10.1371/journal.pone.0246052
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of susceptible and resistant flax seedlings after Fusarium oxysporum lini infection

Abstract: In this study transcriptome was analyzed on two fibrous varieties of flax: the susceptible Regina and the resistant Nike. The experiment was carried out on 2-week-old seedlings, because in this phase of development flax is the most susceptible to infection. We analyzed the whole seedlings, which allowed us to recognize the systemic response of the plants to the infection. We decided to analyze two time points: 24h and 48h, because our goal was to learn the mechanisms activated in the initial stages of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The resistant plants exhibited a sharp, prolonged response to the infection as early as the third dpi. In line with previous work [9][10][11], we observed changes in expression of genes controlling membrane remodelling, secondary metabolite synthesis, synthesis of lipids and cytochrome-related proteins, transcription factors in response to infection. Furthermore, an activation of Germin-like genes provides a clear indication of flax response to the biotic stress associated with disease progression.…”
supporting
confidence: 91%
“…The resistant plants exhibited a sharp, prolonged response to the infection as early as the third dpi. In line with previous work [9][10][11], we observed changes in expression of genes controlling membrane remodelling, secondary metabolite synthesis, synthesis of lipids and cytochrome-related proteins, transcription factors in response to infection. Furthermore, an activation of Germin-like genes provides a clear indication of flax response to the biotic stress associated with disease progression.…”
supporting
confidence: 91%
“…Pathogen-related proteins, components of the cell wall, transcription factors, secondary metabolites and antioxidants all play essential roles in the response of flax to the F. oxysporum f.sp. lini infection, as demonstrated by several transcriptomics experiments [19][20][21].…”
Section: Introductionmentioning
confidence: 75%
“…Recently, several high-throughput transcriptomics experiments provided a general insight into flax resistance to pathogens [19][20][21]. However, the identification of potential key candidate genes in the control of resistance is challenging due to a systemic effect inflicted by infection and, consequently, an unfeasibly large number of genes to be interrogated in focused follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier study reported that transgenic flax plants overexpressing the β-1,3-glucanase gene showed lower susceptibility to this pathogen ( Wróbel-Kwiatkowska et al, 2004 ). The transcriptomal response of the resistant flax cultivar was found to be quicker and more effective allowing translation to a higher number of activated and repressed genes in response to infection by F. oxysporum lini ( Boba et al, 2021 ). The numbers of the differentially expressed PR genes in resistant variety were higher initially (24 hpi) but similar later (48 hpi) in comparison to susceptible variety further established that the degree of the response plays deciding role in the differential resistance reaction, even though the similar qualitative response.…”
Section: Transcriptomicsmentioning
confidence: 99%